Implementation of Collaboration Between Affiliators and Brands: A Phenomenological Study in the Fashion Industry Through Social Media - Hasibuan, Siti Hawa; Kusmilawaty, Kusmilawaty; Irham, Mawaddah (Almana : Jurnal Manajemen dan Bisnis, 2025)
Social media has transformed marketing, with the fashion industry leveraging affiliate collaborations to blend personal narratives and product promotion. Despite Indonesia’s $8.6 billion social commerce market (2022), challenges like mismatched expectations and authenticity crises persist. This study aims to (1) explore affiliators’ subjective experiences in partnering with fashion brands, (2) identify collaboration mechanisms, (3) analyze challenges, and (4) assess partnership effectiveness. A phenomenological approach was adopted, with thematic analysis of open-ended questionnaires from 13 active affiliators. Two dominant models emerged: affiliate links and product bartering. Challenges included task-reward imbalances and restrictive brand guidelines. Effectiveness was measured via audience engagement, click-through rates, and personal branding gains. Successful collaborations require aligned values, transparent communication, and creative flexibility, offering actionable insights for affiliators and brands.